Research on the Transformation Efficiency of Scientific and Technological Achievements of Minis-try-affiliated Universities Based on Network DEA - Jia, Xunliang; Wang, Chuchu (International Journal of Global Economics and Management, 2024)
Previous studies on the transformation of scientific and technological achievements in universities were based on the black box model, and the results obtained were not comprehensive enough. This paper divides the transformation of scientific and technological achievements of universities into the knowledge research and development stage and the value transformation stage. The two-stage network DEA model is used to study the transformation efficiency of scientific and technological achievements of 55 subordinate universities based on the data from 2009 to 2017.The research in this paper finds that the overall efficiency of the transformation of scientific and technological achievements in Chinese universities is relatively stable, and the efficiency of the knowledge research and development stage is relatively high, but the efficiency of the value realization stage is seriously low, resulting in a low level of overall efficiency."985" engineering colleges and "double first-class" colleges have higher input and output efficiency, and cluster analysis is used to classify and summarize the technological transformation of each college. Finally, corresponding development suggestions are put forward.